Food Rituals as Signs of Submission and Symbols of Feminine Marginalization in Maria Messina’s Writings - Bombara, Daniela (I.S. MED. - Interdisciplinary Studies on the Mediterranean, 2025)
Maria Messina (1887-1944) portrays women confined to subservience, unable to challenge male dominance and resigned to their fates, during a transitional period between enduring patriarchy and an unattainable modernity. Her works depict a world fixated on decorum and tradition, a stifling reality where attempts at change merely reaffirm the existing order. The assertion of male authority is deeply intertwined with rituals dictating domestic life, particularly those related to meals. In La casa nel vicolo (1921), the despotic Don Lucio enforces strict schedules and precise procedures for meal preparation, using them to test the loyalty and submission of the women under his control. These rigid customs suppress any aspiration for independence. On the other hand, Messina’s women are often unaware of their subjugation. In La porta chiusa (Le briciole del destino, 1918), Ienna, confined to her room by illness, nostalgically recalls her kitchen ‘domain’, but this perceived authority is illusory, as her husband’s affair with the maid elevates the latter to the true mistress of the household. Attempts to defy traditional roles end in failure: in L’amore negato (1928), Severa’s rejection of her role as a house-wife leads to her downfall. Unlike later Sicilian literature, Messina refrains from lavish descriptions of meals. Her female characters eat hurriedly and in isolation, excluded from sensory enjoyment. Food, consumed without savor, becomes a potent metaphor for lives stifled by emotional and existential deprivation. These women, resigned to barren existences, are left only with ‘the crumbs of life’, as poignantly reflected in the title of Messina’s 1918 collection.